A Study on The Crack Behavior of Jute-Polyester Composites - Saferi, Rozi (Kopertis Wilayah X)
Natural fiber composites are an alternative for replacing environmentally harmful synthetic materials and help control pollution problems. In addition, they are low cost, have better mechanical properties and require low production energy consumption. Also, using such materials in construction works, it is possible to improve the sustainability by eliminating construction wastes. The purpose of this paper is to investigate the crack propagation of bending test on jute fiber-reinforced resin composites with orientation of 90Â° and 45Â°. In this study Jute fiber was spun with a diameter 1.5 mm and arranged into two layers with orientation 90o and 45o . Itâs usedÂ a matrix of clear resin type polyester with a volume fraction 5:95. Bending test specimen is based on ASTM D5045. The results showed that composites with 45o fiber orientation had greater value of crack propagation thanÂ composites with 90o fiber orientation. The elastic energy of composites with 45o fiber orientationÂ tend to decrease dramatically as the initial crack length increases.